Peningkatan Kinerja Pemasaran UMKM Melalui Content Marketing dan Adopsi E-Commerce: Mengkaji Peran Digital Customer Engagement - Andry Herawati; Sri Utami Ady; Nur Sayidah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study examines the effect of content marketing and e-commerce adoption on the marketing performance of micro, small, and medium enterprises (MSMEs), with digital customer engagement as a mediating variable, using a PLS-SEM approach. Data were collected through a survey of 160 MSME actors in Blitar and analyzed using SmartPLS 4. The results indicate that content marketing and e-commerce adoption have a positive and significant effect on digital customer engagement; however, neither variable has a direct effect on marketing performance. Digital customer engagement is found to have a strong influence on marketing performance and to fully mediate the relationship between content marketing, e-commerce adoption, and marketing performance. These findings highlight that the success of digital marketing strategies among MSMEs in the digital era depends largely on the ability of business actors to build and sustain customer engagement, rather than merely adopting digital content or e-commerce platforms to enhance competitiveness.